Mutation Breeding of Thai Native Torenia (Torenia fournieri Lind.) by gamma-ray irradiation - Taychasinpitak, Thunya; Kikuchi, Shinji; Jala, Anchalee; Thanananta, Theerachai; Chanchula, Nattapong (Thai Journal of Science and Technology, 2016)
Abstract Gamma ray irradiation is an effective technique to induce mutations for plant breeding. The aim of this research was to develop new cultivars of Torenia (Linderniaceae) for the ornamental market. Axillary buds (1 node cuttings) of new Thai native Torenia fournieri Lind. were exposed to acute (Cs-137) gamma ray irradiation at 0, 20, 40, 60, 80 and 100 grays. After transplantation, the survival rate and plant height were measured at 60 d after irradiation. Plant height information was used for calculation of GR50. The results showed that GR50 was 68.83 grays. Therefore, axillary buds derived from the first generation of selected mutants were then re-irradiated at 0, 60, 65, and 70 grays. Morphological screening for mutations revealed 3 mutated phenotypes (pink, dark and wavy shaped flowers). The chromosome numbers (2n=2x=18) were not changed after analysis by fluorescence in situ hybridization (FISH). The pollen of mutants with wavy flower shape was sterile. The plants with pink, dark and wavy petals were selected for development of new cultivars. Keywords: Torenia; gamma irradiation; FISH; mutation; axillary bud